1996
DOI: 10.1093/oxfordjournals.annonc.a010489
|View full text |Cite
|
Sign up to set email alerts
|

Two consecutive phase II studies of oxaliplatin (L-OHP) for treatment of patients with advanced colorectal carcinoma who were resistant to previous treatment with fluoropyrimidines

Abstract: SummaryBackground: Oxaliplatin (L-OHP) is a platinum complex that possesses activity against human and murine cells in vitro and in vivo, including colorectal carcinoma-derived cell lines, and cells that have been selected for resistance to cisplatin. We report two consecutive phase II trials of L-OHP for treatment of patients with advanced colorectal carcinoma.Patients and methods: Fifty-eight patients were entered in study I, and 51 patients in study II. All of the patients had tumor progression when they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(140 citation statements)
references
References 6 publications
4
129
0
7
Order By: Relevance
“…This kind of toxicity has been sporadically reported in clinical trials focusing on the effectiveness of OHP in chemotherapy or described as case reports (Machover et al, 1996;Diaz Rubio et al, 1998;Tournigand et al, 1998;Larzilliere et al, 1999;Medioni et al, 1999;De Gramont et al, 2000;Dold et al, 2002;Monnet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of toxicity has been sporadically reported in clinical trials focusing on the effectiveness of OHP in chemotherapy or described as case reports (Machover et al, 1996;Diaz Rubio et al, 1998;Tournigand et al, 1998;Larzilliere et al, 1999;Medioni et al, 1999;De Gramont et al, 2000;Dold et al, 2002;Monnet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Response rates are rarely (and then not reproducibly) above 10% with any of the new agents tested [20]. Oxaliplatin has also a relatively low activity as single agent in second line treatment [21,22], but one small phase II trial reported an unusual high response rate in second line treatment with the combination of oxaliplatinÐ5-FU/LV [23].…”
Section: Discussionmentioning
confidence: 99%
“…Two phase II multicentre studies have evaluated oxaliplatin as second-line monotherapy in a total of 109 patients with histologically proven colorectal adenocarcinoma (Machover et al, 1996). All patients were resistant to 5-FU and had non-resectable metastases, but they were in good general condition.…”
Section: Second-line Treatmentmentioning
confidence: 99%
“…Examples of the clinical trials undertaken with oxaliplatin are outlined below (Levi et al, 1992;BertheaultCvitkovic et al, 1996;Bismuth et al, 1996;Machover et al, 1996; Becouarn et al, 1997; Giacchetti et al, 1997 The results of this study are shown in Table 1. A partial response was achieved in 10 of the 37 evaluable patients, giving an overall response rate of 27%, which is in line with the rate expected for 5-FU/leucovorin as first-line treatment.…”
mentioning
confidence: 98%
See 1 more Smart Citation